Neurotoxic effects of Alicia mirabilis and Aurelia aurita venoms on Callinectes sapidus Rathbun, 1896: behavioural results - Nurçin Killi; Gian Luigi Mariottini; İlkay Tekin; Khouloud Azaiez (Journal of Biological Research)
Cnidaria constitute an important phylum of venomous animals, several of which have a significant impact on human health and activities. Cnidarian venoms are included in a special capsule called nematocyst, and are known to consist of peptides, proteins, phospholipids, glycoproteins, sterols, bioactive amines and carbohydrates. Cnidarian venoms are used for hunting and defence, and have paralytic, neurotoxic, cytotoxic, dermotoxic and hemolytic effects on other living organisms. In this study, the neurological and behavioural effects of different doses of venom obtained from the nematocysts of Alicia mirabilis and Aurelia aurita were observed on blue crabs (Callinectes sapidus) individuals. For this purpose, various doses of venoms were injected on the linkage between merus and carpus parts of the cheliped of blue crab individuals. The most common effects of A. mirabilis and A. aurita venoms were observed to be stiffness and trembling behavior in the legs. These symptoms indicate that venom causes neural paralytic syndrome. It has been observed that the effect of venom increases with time and paralysis occurs before death.